2008
DOI: 10.1111/j.1600-051x.2008.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and periodontitis: an update on the associations and risk

Abstract: Periodontitis may contribute to cardiovascular disease and stroke in susceptible subjects. Properly powered longitudinal case-control and intervention trials are needed to identify how periodontitis and periodontal interventions may have an impact on cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
144
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(157 citation statements)
references
References 202 publications
(242 reference statements)
6
144
0
5
Order By: Relevance
“…On the other hand, as oral examinations for workers in general workplaces are conducted based on employer voluntarism, few companies provide workplace oral examination. Recent studies have suggested that periodontal disease might affect systemic health status with respect to conditions such as diabetes, cardiovascular disease, and metabolic syndrome [4][5][6][7] . Therefore, maintaining good oral health of employees may contribute to good systemic health.…”
mentioning
confidence: 99%
“…On the other hand, as oral examinations for workers in general workplaces are conducted based on employer voluntarism, few companies provide workplace oral examination. Recent studies have suggested that periodontal disease might affect systemic health status with respect to conditions such as diabetes, cardiovascular disease, and metabolic syndrome [4][5][6][7] . Therefore, maintaining good oral health of employees may contribute to good systemic health.…”
mentioning
confidence: 99%
“…Obesity and periodontitis have been associated with changes in lipid metabolism, thus potentially increasing cardiac risk among patients presenting one or both factors 6,8 . Those authors report the existence of a dose-dependent relationship among metabolic serum markers, elevated white blood cell count, and a higher severity of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other meta-analyses also reported that periodontal diseases led to an increased risk of developing CVDs 7,8 . Besides, some researchers postulated that the relationship between periodontitis and CVDs occurs due to the colonization of periodontal microorganisms in atheromatous plaques 7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, experimental evidence has showed that periodontal pathogenic bacteria, mainly Porphyromonas gingivalis, play a role in atherogenesis [12]. Several reviews have described the relationship between periodontal periodontal disease and risk of coronary heart disease or other CVD, and have suggested that periodontitis may contribute to CVD in susceptible subjects [13] [14].…”
Section: Introductionmentioning
confidence: 99%